STRATEGI GURU DALAM MENGAJARKAN KEMAMPUAN LITERASI MEMBACA PERMULAAN ANAK USIA 5–6 TAHUN DI TK MUSLIMAT NU 27 MALANG - Rizka Novitalia; Ahmad Yusuf; Muhammad Arafik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early reading literacy skills are a crucial foundation for children's academic development. Teachers play a strategic role in designing and implementing learning strategies that are appropriate to the characteristics of children aged 5–6 years. This study aims to describe school support for teachers, teachers’ efforts in teaching early reading literacy skills, and challenges faced by teachers in implementing early reading literacy strategies at TK Muslimat NU 27 Malang. This study employed a descriptive qualitative approach with a single-case study design. The research subjects included the principal and group B teachers. Data were collected through semi-structured interviews, non-participant observations, and documentation. Data analysis followed the Miles, Huberman, and Saldana model, consisting of data collection, data condensation, data display, and conclusion drawing. Data trustworthiness was ensured through credibility, transferability, dependability, and confirmability. The findings indicate that the school has provided support through planning, implementation, mentoring, and evaluation; however, further optimization is required, particularly in teacher training and the use of digital learning media. Teachers applied direct instruction and individualized strategies, but their implementation has not been fully optimal due to limited learning media, differences in children’s abilities, and low literacy support from the home environment. Strengthening teachers’ digital competencies and school–parent collaboration is recommended to enhance early reading literacy development.